Estimating Risk Factors for Cesarean Delivery in a Teenage Population [5K]. (May 2017) - Oben, Ayamo G.; Rodriguez, Emma; Nkele, Chika; Springer, Lauren; Acosta, Ometeotl
Abstract : INTRODUCTION: Factors such as advanced age, increased body mass index, extremes of neonatal birth weight among others are predictors of delivery via cesarean section. However, some of these predictors may not applicable to a teenage population. As such, our objective was to identify modifiable predictors for prevention of the primary cesarean delivery, in a nulliparous teen population of a tertiary care center. METHODS: We performed a retrospective cohort chart review of all teenage deliveries (⩽19 years old) at one institution over a 2-year period. The inclusion criteria were all singleton births from July 2014 to July 2016 among mothers at term who delivered via non-elective cesarean section. Exclusion criteria included fetal malpresentation, presentation to prenatal care at gestational age >20 weeks and pregnancies complicated by fetal anomalies. RESULTS: Of the 322 included deliveries, 14.6% delivered by non-elective C-section. The population was 90% Hispanic with a mean age of 17.7 years ± 1.31. Only neonatal birth weight was significantly associated with delivery via cesarean section in bivariate analysis and remained a predictor. Mothers of neonates with extremes of birth weights (< 2500, >4000 g) had higher odds of having a cesarean delivery, compared to neonates with normal birth weight (OR 4.7 95%CI 2.3 – 9.4 and OR 4.6 95% CI 1.1 – 19.4). CONCLUSION: Among adolescent nulliparous patients, birth weight of the neonate was found to be a risk factor that places the gravid teen at increased risk for cesarean delivery. Further research with a greater sample size over a 10-year period is under way.